UPAYA JEPANG MENYEBARKAN BAHASA JEPANG DALAM MERUBAH CITRA NEGARA MELALUI JAPAN FOUNDATION DI INDONESIA PERIODE : 2015-2018 - Fikri Kenjiro Hakeem (2021)
This study aims to explain Japan's efforts to spread Japanese Language in Indonesia through the Japan Foundation and explain the programs created by this Institute with the aim of changing the bad image of Japan in Indonesia after World War II. This problem will be analyzed with the theory of Cultural Diplomacy and Nation Branding which explains and analyzes how the Japan Foundation uses Language as an instrument of Cultural Diplomacy to achieve its goals.